2014
DOI: 10.1080/09168451.2014.930323
|View full text |Cite
|
Sign up to set email alerts
|

The enhancing effect of fucoidan derived from Undaria pinnatifida on immunoglobulin production by mouse spleen lymphocytes

Abstract: In this study, we revealed that a Mekabu (Udaria pinnantifida) extract enhanced immunoglobulin (Ig) production of mouse spleen lymphocytes. Furthermore, it was suggested that water-soluble and high molecular weight ingredients in the Mekabu extract have significant enhancing effect on Ig production. Therefore, fucoidan was estimated as the active component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Fucoidan’s immunomodulatory effects have been reported in different experimental models. It has been shown to activate and promote the maturation of human monocyte-derived dendritic cells [17], and stimulate lymphocyte [18,19] and macrophage activity [18,20] in vitro. According to Do et al [21], fucoidan is an immunomodulating nutrient which alters the sensitivity of glia and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan’s immunomodulatory effects have been reported in different experimental models. It has been shown to activate and promote the maturation of human monocyte-derived dendritic cells [17], and stimulate lymphocyte [18,19] and macrophage activity [18,20] in vitro. According to Do et al [21], fucoidan is an immunomodulating nutrient which alters the sensitivity of glia and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that fucoidan has anticancer effects, which are mainly caused by an inhibition of cancer cell growth and promotion of antitumor cytokine secretion, as well as lymphocyte proliferation [17,18]. It has also been reported that fucoidan induces apoptosis and cell cycle arrest in a variety of cancer cell types, including leukemia, hepatocellular carcinoma, prostate cancer, breast cancer and bladder cancer [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan can target multiple receptors, such as scavenger receptors, or signaling molecules in various cell types, including tumor cells and immune cells 13 14 . Numerous studies have shown that fucoidan has antitumor effect which is mainly manifested as inhibition of tumor cell growth and migration, promoting lymphocyte proliferation and antitumor cytokine secretion 15 16 17 . Our previous studies have shown that fucoidan induce a functional maturation of human monocyte-derived dendritic cells 18 and inhibit monocytes-induced angiogenesis 19 .…”
mentioning
confidence: 99%